Peningkatan Pengetahuan Ibu-Ibu PKK Desa Papahan, Kecamatan Tasikmadu Mengenai Bakteri Escherichia coli Dalam Berbagai Makanan Di Pusat Jajanan Surakarta (Galabo) - Liss Dyah Dewi Arini; Saryadi Saryadi; Nabilatul Fanny (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
The mother is the leader figure in a family who is responsible for managing the family's healthy food needs. Knowledge regarding hygienic food among PKK mothers in Papahan Village, Tasikmadu is still limited, because many of them come from underprivileged families and have less educational background, so basic knowledge from the family is not optimal (less attention is paid to it). This community service activity aims to provide understanding to PKK women about healthy and hygienic food, provide counseling to PKK women about the characteristics of healthy and hygienic food and provide awareness to the public not to buy food carelessly. The outreach method is carried out using the lecture method and explanations regarding healthy and hygienic food and contamination or bacterial contamination in siomai sauce from traveling sellers using posters and power points. The result of this community service activity is that PKK women understand about healthy and hygienic food as well as food that is contaminated or contaminated with bacteria, especially in the example of ten foods sold at the Solo Snack Center (Galabo). The conclusion of this community service activity is that PKK mothers can find out the benefits of healthy and hygienic food for the body and PKK mothers are aware to be more careful in buying food outside so that family health, especially school children, is more secure and mothers PKK mothers understand how to choose healthy and hygienic food for their families.